(untitled) (UUM Journal of Legal Studies, 2014)
The provision for a minimum age of criminal responsibility (MACR) is stated in a number of international children’s rights instruments. The preamble of the United Nations Convention on the Rights of the Child (UNCRC) states that a child, by reason of his physical, mental and emotional immaturity is in need of special safeguards, care and assistance. Despite remarkable improvements in a number of provisions, an examination of the Iran’s laws and regulations reveal that the provision of MACR is currently in conflict with the international instruments particularly the UNCRC. This is despite the fact that Iran is a State Party of the UNCRC since. Furthermore, the Iranian Civil Code expressly provide that the government is to implement the UNCRC provisions as an international treaty. This article critically examines the position of the MACR and punishments of children in the new Islamic Punishment Act of Iran (2013) based on the four Islamic categories of punishments namely Hadd, Qisas, Diya and Ta’zir as enshrined in the new Act. The current article places emphasis on the examination of the issue of MACR in Iran and how effectively it is addressed by the new Act. The nature of this research is doctrinal by examining the new Act of Iran 2013 with a critical legal overview on the Articles relating to children and their impact on the rights of children. Furthermore, it compares the relevant Articles on MACR and punishments of the new Act with the previous abolished Act and the international standards. The purpose is to highlight both the limitations and advancements of the new Act. In the final analysis, this article concludes that despite the improvements in the field of children’s rights in the new Act, it still poses potential risks for the rights of the children in Iran.